Temporal Analysis of Forest Fragmentation in the Amazon Rainforest of Tocantins State, Brazil - Thaiana Brunes Feitosa; Milton Marques Fernandes; Márcia Rodrigues de Moura Fernandes; Renisson Neponuceno Araújo Filho (Floresta e Ambiente, 2023)
Abstract The Amazon Rainforest presents intense pressure from agricultural and cattle farming activities on its forest remnants, which promotes forest fragmentation. The present study aimed to quantify structural changes in the Amazon Rainforest landscape in the state of Tocantins, Brazil, that occurred between 1985 and 2020 using Mapbiomas data and landscape metrics. MAPBIOMS images were used to delimit forest fragments and size classes. Landscape metrics were estimated using the Fragstats® software. In the state of Tocantins, the Amazon Rainforest, grassland, and savanna showed a fragmentation process between 1985 and 2020, with a reduction in their total area and the number of fragments, with less rounded shapes and loss of core areas, in need of environmental policies to protect forest remnants and interrupt the process of Forest fragmentation, especially the Amazon Rainforest.